VIBRATION OF ORTHOTROPIC DOUBLY CURVED PANEL WITH A SET OF HINGED INCLUSIONS OF ARBITRARY CONFIGURATION - Шопа, Тетяна Василівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the framework of the refined theory, which takes into account transverse shear deformation, the solution of the problem on the steady state vibrations of the orthotropic doubly curved panel with the arbitrary number of simply supported rigid inclusions of the arbitrary geometrical form, orientation, and location is constructed. External boundary of the panel is of the arbitrary geometrical configuration. Arbitrary harmonic in time boundary conditions are considered on the external boundary of the panel. The solution is built on the basis of the indirect boundary elements method and the sequential approach to the representation of the Green's function. The boundary value problem is reduced to the system of algebraic equations.